2014
DOI: 10.4172/2329-891x.1000142
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antiretroviral Therapy in HIV-Positive Patients in Ethiopia: Review

Abstract: Background: Highly active antiretroviral therapy (HAART) offered HIV-positive individuals tremendous lifesustaining benefits. The benefits are sustainable only through optimal adherence. This systematic review was conducted to synthesize the available studies in order to determine average adherence, identify variables associated with adherence and shed light on the design and improvement of adherence studies and interventions. Method: Studies were selected from electronic databases (Pubmed, Hinari, Google scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…11 The report from different studies conducted in Ethiopia revealed that the level of optimal adherence ranges from 72.4% to 94.3%, which indicates that HAART adherence is remaining suboptimal. 12 The roots of poor adherence to HAART are extremely varied, and adherence is associated with many individuals and facility-related factors. The findings of studies carried out in some developing countries like India, Nepal, Togo, and Nigeria identified that females, daily alcohol consumers, and people with depressive symptoms are less likely to adhere to HAART.…”
Section: Introductionmentioning
confidence: 99%
“…11 The report from different studies conducted in Ethiopia revealed that the level of optimal adherence ranges from 72.4% to 94.3%, which indicates that HAART adherence is remaining suboptimal. 12 The roots of poor adherence to HAART are extremely varied, and adherence is associated with many individuals and facility-related factors. The findings of studies carried out in some developing countries like India, Nepal, Togo, and Nigeria identified that females, daily alcohol consumers, and people with depressive symptoms are less likely to adhere to HAART.…”
Section: Introductionmentioning
confidence: 99%
“…There is a dearth of literature on use of standardized scales to measure medication adherence among people on ART in Ethiopia. A systematic review of 15 ART adherence studies in Ethiopia reported that 60% of the studies used self-reports, other methods included: caregiver reports, unannounced pill counts, pharmacy refill record, medication event monitoring systems, viral load measurement, CD4 count and record review [17]. Some studies have reported challenges associated with various methods of assessing adherence among users of ART in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies reported that self-reports overstated adherence levels compared to unannounced pill count due to social desirability bias, in addition to being susceptible to recall bias [19,20]. The authors reported that despite their limitations, self-reports and pill count are widely used in Ethiopia because they are cheaper and easy to implement [17]. Self-reports have also been found to correlate with viral load and clinical outcomes [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation